The Impact Of Transformational Leadership And Motivation On Employee Performance With Job Satisfaction As Intervening Variable In Indonesian Banking Industry During Digital Transformation - Lindawati, Mesra; Parwoto, Parwoto (Journal of Industrial Engineering & Management Research, 2021)
Digital transformation is currently a very important agenda in the Indonesian Banking Industry. The era of globalization, and changes in customer transaction preferences during the Covid 19 pandemic, have encouraged companies to make various changes related to technology. Being adaptive and agile throughout the process is one of the foundations in maintaining the reliability and sustainability of the company. However, drastic changes and various uncertainties that arise during the transformation process can affect various aspects of human resources, such as motivation, job satisfaction and performance. In this study, the effect of transformational leadership and employee motivation on employee performance will be calculated through job satisfaction as an intervening. This research was conducted at a private bank in Indonesia with 95 respondents located in Tangerang, an industrial area located near the Indonesian capital city. Sampling using purposive sampling technique and the type of research is quantitative. Collecting data using a survey method through distributing questionnaires using a likert scale, the analysis method using SEM-PLS. The results of data analysis show that transformational leadership has a positive and significant effect on employee performance through job satisfaction. Direct work motivation has no significant effect, but through job satisfaction it has a positive and significant effect on employee performance.